Contributions of GeoGebra in the dialectics of a didactic situation for the study of Central Tendency Measures - José Ronaldo Alves Araújo; Celina Aparecida Almeida Pereira Abar (Educação Matemática Debate, 2019)
In this article we reflect on the contributions of GeoGebra in the dialectics of a didactic situation involving Central Tendency Measures. From the results of a master's research that aimed to investigate the potentialities of GeoGebra for the study of Central Tendency Measures, which were presented at the XIII Encontro Nacional de Educação Matemática. From the theoretical point of view the study resorted to dialectics of action, formulation and validation and institutionalization, present in the Theory of Didactic Situations. In a qualitative approach, Didactic Engineering assumptions were adopted to develop apply and analyze the sequence of activities. Applied to students graduating from the 9th grade of elementary school, the results of the study showed that in the proposed activities, in the different dialectics, the multiple representations of the data in GeoGebra constituted a didactic advantage which contributed to the understanding and analysis of the data, contributing to the study of Central Tendency Measures.